2022
DOI: 10.1002/jobm.202200155
|View full text |Cite
|
Sign up to set email alerts
|

Time‐series gene expression patterns and their characteristics of Beauveria bassiana in the process of infecting pest insects

Abstract: Beauveria bassiana has been widely used as an important biological control fungus for agricultural and forest pests, and clarifying the interaction mechanism between B. bassiana and its host will help to better exert the efficacy of the mycoinsecticide. Here, we proposed a novel pattern analysis (PA) method for analyzing time-series data and applied it to a transcriptomic data set of B. bassiana infecting Galleria mellonella. We screened out 14 patterns including 868 genes, which had some characteristics that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…However, the ratio of upregulated to downregulated DEGs was reversed when the duration of infection was shorter (i.e., 3-12 h p.i.) or when exposed to a strain of B. bassiana with low virulence [40][41][42]. The potent pathogenicity of the wild-type B. bassiana strain used in this study likely contributed to the higher number of downregulated DEGs observed in P. puparum.…”
Section: Discussionmentioning
confidence: 95%
“…However, the ratio of upregulated to downregulated DEGs was reversed when the duration of infection was shorter (i.e., 3-12 h p.i.) or when exposed to a strain of B. bassiana with low virulence [40][41][42]. The potent pathogenicity of the wild-type B. bassiana strain used in this study likely contributed to the higher number of downregulated DEGs observed in P. puparum.…”
Section: Discussionmentioning
confidence: 95%